1998
DOI: 10.2307/2992001
|View full text |Cite
|
Sign up to set email alerts
|

Management and Restoration Ecology of the Federal Threatened Mead's Milkweed, Asclepias meadii (Asclepiadaceae)

Abstract: The federal threatened Asclepias meadii Torr. (Aselepiadaceae) is a perennial, self-incompatible prairie fori) imperiled by habitat destruction and population fragmentation. Many large populations persist in prairie haymeadows in Kansas and Missouri despite removal of seed pods by annual summer mowing. Only a few small populations remain in Illinois. Iowa, and northern Missouri. Recovery of these small populations and restoration of new populations are recovery objectives lor this species. This study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 14 publications
(28 reference statements)
1
27
0
Order By: Relevance
“…Previous studies of A. meadii favored juveniles over seeds as restoration units because the observed germination and seedling growth rates were higher in the greenhouse than the field Bowles et al, 2001), patterns also seen in this study. A. meadii appears to require a threshold size before it begins to flower (Bowles et al, 2001). As a consequence, plants started in the greenhouse may have a quicker path to maturity than those in the field.…”
Section: Discussion Propagule Selection For Restorationsupporting
confidence: 78%
See 1 more Smart Citation
“…Previous studies of A. meadii favored juveniles over seeds as restoration units because the observed germination and seedling growth rates were higher in the greenhouse than the field Bowles et al, 2001), patterns also seen in this study. A. meadii appears to require a threshold size before it begins to flower (Bowles et al, 2001). As a consequence, plants started in the greenhouse may have a quicker path to maturity than those in the field.…”
Section: Discussion Propagule Selection For Restorationsupporting
confidence: 78%
“…5 53). Previous work by Bowles et al (1998) noted a correspondence between higher than average May-Jul. rainfall and increased seedling survivorship.…”
Section: Resultsmentioning
confidence: 86%
“…Bowles et al (2001) reported an average survival rate of 0.35 (survival to the end of the first growing season) for planted seeds at seven prairie sites. At three of these sites, Bowles et al (1998) observed greater survivorship and larger individuals in burned sections of the sites than in unburned sections, with effect size of 0.85 (logit scale) being the largest observed. In our model, we specified a 0.35 juvenile survival rate in any year that the site was not burned and 0.56 in any year that it was burned, the difference corresponding to this effect size (Table 1).…”
Section: Predictive Modelsmentioning
confidence: 84%
“…Average fecundity is consistently reported around 60 seeds per pod (Betz 1989;Betz and Lamp 1992;Bowles et al 1998;Row et al 1999), with no evidence of firerelated differences. In our model, we used the range provided by Betz (1989) and permitted fecundity to vary uniformly between 55 and 68 seeds per pod on both burned and unburned sites (Table 1).…”
Section: Predictive Modelsmentioning
confidence: 96%
See 1 more Smart Citation